2006
DOI: 10.1007/s10681-006-9104-9
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Using Spectral Reflectance Indices to Estimate Yield in Wheat Grown Under Reduced Irrigation

Abstract: The objectives of this research were to study the association in bread wheat between spectral reflectance indices (SRIs) and grain yield, estimate their heritability, and correlated response to selection (CR) for grain yield estimated from SRIs under reduced irrigation conditions. Reflectance was measured at three different growth stages (booting, heading and grainfilling) and five SRIs were calculated, namely normalized difference vegetation index (NDVI), simple ratio (SR), water index (WI), normalized water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 38 publications
12
77
0
Order By: Relevance
“…It was reported earlier that normalizing can improve the relationship over a ratio index (Tucker, 1979). Babar et al (2006aBabar et al ( , 2006b reported that the normalized index did not produce signifi cantly better results over the ratio index for predicting yield and biomass in spring wheat. This is also evident in our studies.…”
Section: Correlation Between Sri and Grain Yieldmentioning
confidence: 95%
See 1 more Smart Citation
“…It was reported earlier that normalizing can improve the relationship over a ratio index (Tucker, 1979). Babar et al (2006aBabar et al ( , 2006b reported that the normalized index did not produce signifi cantly better results over the ratio index for predicting yield and biomass in spring wheat. This is also evident in our studies.…”
Section: Correlation Between Sri and Grain Yieldmentioning
confidence: 95%
“…The water-based indices showed an advantage over the vegetation-based indices for selecting the higher-yielding genotypes compared to the widely used vegetation-based indices. Ball and Konzak (1993) demonstrated the effi ciency of normalized diff erence vegetation index in selecting higher-yielding genotypes under water nonlimiting conditions using two readings at the grain-fi lling stage, while Babar et al (2006b) reported the higher effi ciency of the near-infrared-based indices for grain yield selection under partially irrigated spring wheat environments. We have shown that the water-based indices are effi cient in selecting higher-yielding genotypes in winter Figure 2.…”
Section: Selection Of Higher-yielding Genotypesmentioning
confidence: 99%
“…Many other studies have identified optimum wavebands for a given application by calculating narrow-band NDVI for all possible waveband combinations for a given hyperspectral sensor (Fu et al, 2014;Hansen and Schjoerring, 2003;Thenkabail et al, 2000;Thorp et al, 2004). Babar et al (2006) demonstrated several narrowband spectral reflectance indices that explained genetic variability in wheat biomass. Mistele and Schmidhalter (2008) measured spectral reflectance of maize canopies from four view angles and found the spectral reflectance indices were strongly correlated (0:57 6 r 2 6 0:91) with total nitrogen uptake and dry biomass weight.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research efforts have been devoted to seeking a quantitative relation between remotely sensed spectral information and crop yields, and consequently obtaining a robust estimation and forecasting for agricultural productions [8,[20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first one is based on crop growth models, which incorporates remote sensing data into agrometeorological or bio-physiological models [23,18,[31][32][33]. For example, Doraiswamy et al (2003) implemented the real-time assessment of the magnitude and variation of crop condition parameters into the crop model called Erosion Productivity Impact Calculator (EPIC) [34].…”
Section: Literature Reviewmentioning
confidence: 99%